Cyprian and the treatise De habitu uirginum: the construction of boundaries among the Christian virgins and the search for purity in the church of Carthage (third century AD) - Soares, Carolline da Silva (Romanitas - Revista de Estudos Grecolatinos, 2013)
The treatise De habitu uirginum was written in 249 AD by Cyprian, bishop of Carthage between 249 and 258. This work presents the praises regarding the Christian virgins, treated as virtuous women, but also indicates the cautions and precautions they should take in relation to the temptations of the world, which may lead them to abandon the pudicitia considered, by the bishop, something sublime and essential to the functioning of the Christian community. Our purpose in this article is to analyze the admonitions and codes of conduct issued by Cyprian in relation to the Christian virgins – for example, the spaces of the city they could and could not attend, as well as how they should dress and behave – as a means of establishing the boundaries between the "true" virgin and preserving the purity within the community in Carthage.